2011
DOI: 10.1590/s0102-695x2011005000033
|View full text |Cite
|
Sign up to set email alerts
|

Anthocephalus cadamba (Roxb.) Miq., Rubiaceae, extract shows hypoglycemic effect and eases oxidative stress in alloxan-induced diabetic rats

Abstract: Abstract:The hydroethanolic extract of the flowering tops of Anthocephalus cadamba (Roxb.) Miq., Rubiaceae, a Bangladeshi medicinal plant, was studied for its potential hypoglycemic effect and antioxidant property in alloxan-induced diabetic rats. The extract induced significant reduction in serum glucose, and transaminases, e.g. aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatases (ALP), activities. Significant changes in the thiobarbituric acid reactive substances (TBARS), perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…All drugs were diluted with saline (0.9%) in established doses and administered orally by gavage in a volume of 0.5 ml/100 g body weight (Trovato et al, 1996;Diehl et al, 2001). Glucose levels were measured before the rats received the treatment (zero time) and 30 min after glucose was administrated (4 g/kg) (Alam et al, 2011;Pereira et al, 2012). Blood samples were collected from the tail vein just prior to and 30, 60 and 180 min after glucose loading, and the glucose level (mg/dl) was assayed by a glucometer (Accu-Chek ® Performa).…”
Section: Oral Glucose Tolerance Curvementioning
confidence: 99%
“…All drugs were diluted with saline (0.9%) in established doses and administered orally by gavage in a volume of 0.5 ml/100 g body weight (Trovato et al, 1996;Diehl et al, 2001). Glucose levels were measured before the rats received the treatment (zero time) and 30 min after glucose was administrated (4 g/kg) (Alam et al, 2011;Pereira et al, 2012). Blood samples were collected from the tail vein just prior to and 30, 60 and 180 min after glucose loading, and the glucose level (mg/dl) was assayed by a glucometer (Accu-Chek ® Performa).…”
Section: Oral Glucose Tolerance Curvementioning
confidence: 99%
“…The dynamic regulation of liver glucose metabolism is vital for systemic carbohydrate homeostasis, and the disorder of insulin secretion could lead to diabetes. Previous studies have reported that various extracts of N.cadamba can reduce the blood glucose level of hyperglycemic mice by increasing the glucose uptake [1,2,5,29]. Based on our bioinformatics prediction, PI3K/Akt pathway were targeted by N.cadamba miRNAs.…”
Section: Discussionmentioning
confidence: 83%
“…All the drugs were administered four times on the first day (1, 2, 4, and 6 h) and single time on 2nd, 4th, 7th, and 14th day. The crude extracts from A. cadamba have been shown to possess biological activities viz., anti-inflammatory [7] antihepatotoxic activities [8], analgesic activity [9], antimicrobial and anthelmintic activities [10] and hypoglycemic activity [11]. The plant, Anthocephalus cadamba has been reported to contain glycans, saponins, glycoproteins, peptides, amino acids, terpenoids, alkaloids and flavonoids as their chief phytochemical constituents which has been credited for hypoglycemic activity [12][13][14].…”
Section: Preparation Of Test Samplementioning
confidence: 99%